The effect of microbiome composition on impulsive and violent behavior: A systematic review - Langmajerová, Michaela; Roubalová, Radka; Šebela, Antonín; Vevera, Jan (Behavioural brain research, 2023)
The impact of the microbiome on brain function and behavior has recently become an important research topic. We searched for a link between the gut microbiome and impulsive and violent behavior. We focused on critical factors influencing the microbiome establishment that may affect human health later in life, i.e., delivery mode, early-life feeding, and early antibiotic exposure. We searched PubMed, Web of Science, and the Cochrane Library. We included original human studies examining adults and children with impulsive and/or violent behavior that assessed the gut microbiota composition of participants, delivery mode, infant feeding mode, or early antibiotic exposure. Bibliographic searches yielded 429 articles, and 21 met the eligibility criteria. Two studies reported data on patients with schizophrenia with violent behavior, while 19 studies reported data on patients with attention-deficit hyperactivity disorder (ADHD). The results showed several bacterial taxa associated with ADHD symptomatology and with violent behavior in patients with schizophrenia. No association was found between delivery mode and impulsive behavior, nor did any articles relate infant feeding mode to violent human behavior. Those studies investigating early antibiotic exposure yielded ambiguous results. The heterogeneity of the data and the different methodologies of the included studies limited the external validity of the results. We found few studies that addressed the possible microbiome involvement in the pathophysiology of impulsive and violent behavior in humans. Our review revealed a gap in knowledge regarding links between the gut microbiome and these extreme behavioral patterns.
Keywords: Gastrointestinal Microbiome; Attention Deficit Disorder with Hyperactivity; Infant; Humans; Impulsive Behavior; kojenec; Impulsive behavior; dítě; Child; hyperkinetická porucha; dospělí; Microbiota; Violence; lidé; antibakteriální látky; Adult; Anti-Bacterial Agents; Dysbiosis; agrese; Attention deficit disorder with hyperactivity; střevní mikroflóra; Aggression; impulzivní chování; Antibiotics